2013
DOI: 10.1111/codi.12059
|View full text |Cite
|
Sign up to set email alerts
|

The relation between lymph node status and survival in Stage I–III colon cancer: results from a prospective nationwide cohort study

Abstract: High lymph node count was associated with improved overall survival in colon cancer. Lymph node ratio was superior to N-stage in differentiating overall survival in Stage III colon cancer. Stage migration was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 28 publications
5
58
0
1
Order By: Relevance
“…3 Furthermore, a large prospective trial and several population-based studies reported that an increase in the number of lymph nodes sampled could improve survival through accurate staging and consequently tailored treatments. [4][5][6] A large body of research has documented that shortterm surgical complications and long-term survival are correlated with hospital volume. [7][8][9] Surgery-related mortality can be avoided if cancer surgeries are performed by high-volume hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…3 Furthermore, a large prospective trial and several population-based studies reported that an increase in the number of lymph nodes sampled could improve survival through accurate staging and consequently tailored treatments. [4][5][6] A large body of research has documented that shortterm surgical complications and long-term survival are correlated with hospital volume. [7][8][9] Surgery-related mortality can be avoided if cancer surgeries are performed by high-volume hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of at least 12 lymph nodes is important for accurate staging and treatment planning and is associated with improved survival 5 . The percentage of breast cancer resections that used breast-conserving surgery rather than mastectomy ranged from 31% to 75% (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous previous studies [18][19][20][21][22][29][30][31][32]39 have shown an association of a low lymph node count and adverse outcome in colon cancer, particularly in stage II. These studies have sensitized surgeons, oncologists, and pathologists for the importance of adequate lymph node examination.…”
Section: Discussionmentioning
confidence: 99%